Changes in mortality rates from acute types of coronary artery disease in Russia for the period from 2015 to 2019 - O. M. Drapkina; M. G. Bubnova; I. V. Samorodskaya; O. A. Akulova; D. M. Aronov (Российский кардиологический журнал)
Aim. To identify regional specifics of changes in mortality rates from acute types of coronary artery disease (CAD) in 82 Russian regions for the period from 2015 to 2019.Material and methods. The study used data from the Federal State Statistics Service of Russia on mortality from acute CAD types in 82 Russian regions. Standardized death rates (SDRs) for 2015 and 2019 were estimated based on the European standard. We analyzed the SDRs of the population from acute (primary) and recurrent myocardial infarction (MI), other acute CAD types (I21-I22, I24.8 in the 10th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10)).Results. Over the period from 2015 to 2019, mortality from all acute CAD types decreased by 21%, from acute MI — by 9%, from recurrent MI — by 22%, from any MI (acute/recurrent) recurrent — by 14%, and from other CAD types — by 21%. A decrease in mortality from all acute CAD types was recorded in 69 regions, from acute MI — in 58 regions, and recurrent MI — in 62 regions. However, a simultaneous decrease in SDRs from each of the acute CAD types (acute MI, recurrent MI and other acute CAD types) for the period 2015-2019 occurred only in 29 Russian regions. An increase in mortality from all acute CAD types was noted in 14 regions and from any MI — in 21 regions. The coefficient of variation (Cv) for recurrent MI and other acute CAD types of 69% and 103%, respectively, in 2015 and its growth (up to 75% and 134%, respectively) by 2019 indicate growing problems with the coding of death causes.Conclusion. In 2019, compared to 2015, a decrease in mortality from acute CAD types was recorded in most Russian regions. The identified regional specifics require clarification of approaches to death cause coding and the introduction of additions to mortality reduction programs, taking into account the specifics of each Russian region.